1995
DOI: 10.1007/bf01411440
|View full text |Cite
|
Sign up to set email alerts
|

Early blood-brain barrier disruption after high-dose single-fraction irradiation in rats

Abstract: We studied the effect of high-dose single-fraction irradiation on the permeability of the blood-brain barrier (BBB) in rat brains. Immunohistochemistry with an antibody to serum albumin was used as a sensitive method for detecting the extravasation of endogenous serum components. Extravasation of albumin was detected as early as 1 day after irradiation with 20 or 40 Gy. Immunoreactivity reached its maximum after 3 days, gradually decreased during the following few weeks and had disappeared by day 30. Extravasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 25 publications
1
28
1
1
Order By: Relevance
“…Vasogenic edema following disruption of the BBB 27 could be an early and readily recognizable pathophysiologic event occurring after irradiation. Nakata et al 28 found that the destruction of the BBB was detectable as early as 1 day after irradiation with 20 or 40 Gy, reached its maximum after 3 days, and gradually decreased during the following few weeks. Yet to the best of our knowledge, no study of the destruction of the BBB and brain edema has been performed in the fractionated-radiation model.…”
Section: Discussionmentioning
confidence: 99%
“…Vasogenic edema following disruption of the BBB 27 could be an early and readily recognizable pathophysiologic event occurring after irradiation. Nakata et al 28 found that the destruction of the BBB was detectable as early as 1 day after irradiation with 20 or 40 Gy, reached its maximum after 3 days, and gradually decreased during the following few weeks. Yet to the best of our knowledge, no study of the destruction of the BBB and brain edema has been performed in the fractionated-radiation model.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the occurrence of a transient increase of BBB permeability after radiation exposure, though the duration seemed to vary among the reports, and it was suggested to strongly depend on the size and the physicochemical properties of the probes used for the assay. 27 Nakata et al 28 studied the effect of single irradiation on the permeability of the BBB in rat brains and found that the destruction of the BBB was detected as early as 1 day after irradiation with 20 or 40 Gy, reached its maximum after 3 days, and gradually decreased during the following few weeks. The degree of this destruction could become much greater when the irradiation dose increased to 80 Gy and the BBB disruption remained during the whole course of the experiment.…”
Section: Figmentioning
confidence: 99%
“…The frequency, 7 intracranial location, 8 mechanism, 9,10 and time evolution of the occurrence of edema after cerebral irradiation 11,12 have been discussed by numerous authors. Helenowski et al 7 investigated 600 patients after linear accelerator irradiation (eight and nine isocenters were used; 65% of the patients had .13.5 cm 3 tumor volume); edema, which could be balanced by steroids, was observed in 30% of the patients.…”
Section: Discussionmentioning
confidence: 99%